Sistem Informasi Supply Chain Management Berbasis Web di Apotik Prima Angel - Rahman, Muhamad; Herdiansyah, Muhammad Izman; Abdillah, Leon Andretti; Andri, A (Jurasik (Jurnal Riset Sistem Informasi dan Teknik Informatika), 2026)
The inventory information system is a digital platform created to make it easier to manage inventory. Technological advances have encouraged business actors to adapt and apply it to their business. Prima Angel Pharmacy is a pharmacy that provides various types of medicines that are registered with BPOM (Food and Drug Supervisory Agency). In managing drug supplies, Prima Angel pharmacies still use conventional methods, which have the risk of errors in recording drug supplies, loss of report documents and damage to report documents regarding drug supplies. To support the process of managing drug supplies well and efficiently, as well as minimizing the risk of harm to the Prima Angel pharmacy, the author designed and built a website-based inventory information system. Having a website-based inventory information system helps make it easier for Prima Angel pharmacies to manage drug supplies, minimize errors in recording drug supplies, and anticipate drug supply shortages. Apart from that, with this digital platform, Prima Angel pharmacies can access reports related to drug supplies quickly and precisely based on accurate data.